1996
DOI: 10.1021/bi952348q
|View full text |Cite
|
Sign up to set email alerts
|

Folding and Unfolding Kinetics of the Proline-to-Alanine Mutants of Bovine Pancreatic Ribonuclease A

Abstract: Four single mutants (P42A, P93A, P114A, and P117A) of bovine pancreatic ribonuclease A (RNase A) in which each mutant has one of the four prolines of RNase A changed to alanine were prepared. The physical properties of these four mutants indicate that their native structure is essentially identical to that of wild-type RNase A. The disulfide-intact forms of these proteins were denatured in guanidine hydrochloride (Gdn.HCl) and then refolded by dilution of the Gdn.HCl. Single-jump folding, single-jump unfolding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
177
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(202 citation statements)
references
References 24 publications
(39 reference statements)
25
177
0
Order By: Relevance
“…RNase A contains four disulfide bonds and four proline residues (two cis and two trans) (Wlodawer et al, 1988), and kinetic folding studies have been carried out both with the disulfide bonds intact (Garel & Baldwin, 1973;Houry et al, 1994;Dodge & Scheraga, 1996) and with the disulfide bonds first reduced and then oxidized (Rothwarf et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…RNase A contains four disulfide bonds and four proline residues (two cis and two trans) (Wlodawer et al, 1988), and kinetic folding studies have been carried out both with the disulfide bonds intact (Garel & Baldwin, 1973;Houry et al, 1994;Dodge & Scheraga, 1996) and with the disulfide bonds first reduced and then oxidized (Rothwarf et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of U,, decreases rapidly as the X-Pro groups isomerize to the equilibrium isomeric-state populations. In a stopped-flow refolding kinetic experiment, U, folds very rapidly to the native structure without requiring peptide-group isomerization (Houry et al, 1994) which, as shown by Brandts et al (1975), would otherwise slow the refolding process.The distribution of cis and trans proline peptide groups in the unfolded state has been deduced from stopped-flow unfolding/ refolding kinetic studies of the wild-type and of proline-to-alanine and tyrosine-to-phenylalanine mutants of RNase A (Dodge & Scheraga, 1996;Houry & Scheraga, 1996;Juminaga et al, 1997).In these studies, the U,, species of the proline-93-to-alanine (P93A) mutant of RNase A exhibited very different kinetic properties than the U , species of wild-type RNase A. The UUf species of P93A converts to other unfolded species (Urn and U,) at a rate that is 20 times greater than that at which the UUf species converts to other unfolded species in wild-type RNase A (Table 7 of Dodge & Scheraga, 1996).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is not rote, as replacing Asn113 and Pro114 with R-Nip-RNip (a diastereomer of R-Nip-S-Nip) eliminates enzymatic activity. Similarly, the transition temperatures for the P114A and P114G variants are decreased by $10 C. [23][24][25] Thus, b 2 -hAla-b 3 -hAla and R-Nip-S-Nip are more than passive linkers 26 -both support native protein structure. This conclusion is supported by the indistinguishable CD spectra of both RNase A and b 2 b 3 hAla RNase A (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 93%